A Review on Multilevel Inverter Topologies - Afshin Balal; Saleh Dinkhah; Farzad Shahabi; Miguel Herrera; Yao Lung Chuang (Ital Publication, 2022)
In this paper, a brief review of the multilevel inverter (MLI) topologies is presented. The two-level Voltage Source Inverter (VSI) requires a suitable filter to produce sinusoidal output waveforms. The high-frequency switching and the PWM method are used to create output waveforms with the least amount of ripples. Due to the switching losses, the traditional two-level inverter has some restrictions when running at high frequencies. For addressing this problem, multilevel inverters (MLI) with lower switching frequencies and reduced total harmonic distortion (THD) are employed, eliminating the requirement for filters and bulky transformers. Furthermore, improved performance at the high switching frequency, higher power quality (near to pure sinusoidal), and fewer switching losses are just a few of the benefits of MLI inverters. However, each switch has to have its own gate driver for implementing MLI, which adds to the system's complexity. Therefore, reducing the number of switches of MLI is necessary. This paper presents a review of some of the different current topologies using a lower number of switches. Doi: 10.28991/ESJ-2022-06-01-014 Full Text: PDF